PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI FAKTOR PEMODERASI BANK PEMBANGUNAN DAERAH TAHUN 2001-2011 - Ayu, Rika Puspa; Emrinaldi, Emrinaldi (Jurnal Tepak Manajemen Bisnis, 2017)
The purpose of this study was to determine the impact of liquidity, leverageand profitability toward firm value and to determine the effect of dividend policy onthe relationship liquidity, leverage and profitability on firm value.The population in thisstudy is the Regional Development Banks registered in Bank Indonesia in 2001-2011 asmany as 24 banks. To determine sample were use purposive random sampling, there wereonly 15 banks that meet the criteria and to analyze the data was used multiple linearregression method.The study states that the leverage (DER) and profitability (ROA) revealeda significant effect on firm value. While the liquidity variable (LDR) declared nosignificant effect on firm value. For moderating variable dividend policy, the results showedthat leverage (DER) with a dividend policy as a moderating variable and profitability(ROA) with dividend policy as a moderating variable declared significant effect on firmvalue . While liquidity with the dividend policy as a moderating variable declared nosignificant effect on firm value.